Genetic diversity and differential in vitro responses to Ni in Cenococcum geophilum isolates from serpentine soils in Portugal - Gonçalves, Susana C. (2011)
ACESSO via B-on: http://dx.doi.org/10.1007/s00572-007-0145-2